Evaluations on heat resistance of curtains with water film in a fire. (3rd July 2016) - Hu, Wei-Chieh; Nurcholik, Samsu Dlukha; Lee, Shin-Ku; Lin, Ta-Hui
Abstract: Fire tests of fireproof and non-fireproof curtains were conducted to investigate the cooling performance of the proposed water film system. The experimental results showed that although commercial fireproof curtains without a water film system had good flame resistance, they had limited heat resistance. The maximum temperature on the unexposed surface of the tested commercial fireproof curtains without a water film system reached 693 °C, and the curtains failed in 30 min. In the cases of curtains with a water film system, the temperature of the unexposed surface was able to remain below 45 °C for the fireproof curtain and 55 °C for the non-fireproof curtain. The integrity of both curtains was conserved for the entire 60-min test duration. Using the proposed water film system, the heat resistance and fire integrity of curtains were greatly improved.